2021
DOI: 10.1186/s13690-021-00581-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual and community-level determinants of childhood vaccination in Ethiopia

Abstract: Background Vaccines are one of our most important tools for preventing outbreaks and keeping the world safe. Most unvaccinated children live in the poorest countries including Ethiopia. Therefore, this study aimed to identify the determinants of vaccination coverage among children aged12–23 months in Ethiopia. Methods A cross-sectional secondary data were obtained from the 2016 Ethiopian Demographic and Health Survey data (EDHS). A total of 1929 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
3
0
0
Order By: Relevance
“…The current study found that children who were born at home were more likely to be non- and incompletely vaccinated than fully vaccinated compared to those who were born in a hospital. This result is in line with studies conducted earlier (17,20,21) , which reported being delivered in the family /home increases the risk of incomplete and non-vaccination. Mothers giving birth in hospitals receive crucial vaccination counselling, while those choosing home birth often have no such access, leaving parents uninformed about critical immunizations (22) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study found that children who were born at home were more likely to be non- and incompletely vaccinated than fully vaccinated compared to those who were born in a hospital. This result is in line with studies conducted earlier (17,20,21) , which reported being delivered in the family /home increases the risk of incomplete and non-vaccination. Mothers giving birth in hospitals receive crucial vaccination counselling, while those choosing home birth often have no such access, leaving parents uninformed about critical immunizations (22) .…”
Section: Discussionsupporting
confidence: 93%
“…In the meantime, considerable proportions (20.2%) of children never received any of these basic vaccines. These findings are comparable with the findings of studies previously conducted elsewhere (7,9,15,17,18) . This low coverage indicates that there is a gap in addressing all children in every district with routine childhood vaccination and challenges to achieve high vaccination coverage remain.…”
Section: Discussionsupporting
confidence: 92%
“…The odds of PCV dropout were higher in children of respondents who reside in emerging regions as compared to those who live in city administrations. In line with what we found, a number of studies showed that region has a significant association with children’s vaccination status ( 25 , 27 , 28 , 42 , 43 ). This could be because most respondents from emerging regions are from remote, hard-to-reach areas, and mothers there are less aware of the advantages of receiving all recommended vaccinations, EPI sessions, and health services.…”
Section: Discussionsupporting
confidence: 92%
“…Mothers' and caretakers' educational status was found to be significantly associated with full vaccination status, as mothers and caretakers who had attended formal education were almost four times more likely to vaccinate their children than those who did not attend formal education. This finding was consistent with other studies performed in other areas of the country [7,11,18]. The findings suggest that complete immunization was more common in children whose mothers were educated, partly because maternal education leads to the acquisition of literacy skills that can be applied to knowledge of vaccination and child protection and better health-seeking behaviours, which then improves immunization uptake for their children.…”
Section: Discussionsupporting
confidence: 91%